Book Review of Economic Theories of Development: An Analysis of Competing Paradigms - Seyed hossein Mirjalili (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The text explains six main intellectual frameworks in the economic theories of development based on Cohen's paradigm. Since the publication of Thomas Kuhn's Structure of Scientific Revolutions in 1962, researchers in the natural sciences and then social sciences, particularly economic researchers tried to apply paradigmatic analysis in a variety of disciplines including development. Hunt’s book is a good example of such works. Modernization, structuralism, Neo-Marxism, Maoism, basic needs, and Neoclassical Economics as competing paradigms have been discussed in this work. The author explains dependency theory, but he does not recognize it as a paradigm. In this paper, the author’s definition of paradigm has been criticized. Another critique to the text is incommensurability of paradigms that constitute the book's approach.Economic methodologists, who viewed economics from the perspective of Cohen’s scientific revolution, have recognized Keynesian economics as a true paradigm shift in economics, and development economists recognized the shift from modernization to dependency theory as a true paradigm shift in development. Finally, institutionalist approach to economic development was neglected and has not been discussed in the text.